Analysis of utterances about the contagion caused by Aedes aegypti in Brazilian campaigns - Anderson Carvalho Pereira (Instituto de Comunicação e Informação Científica e Tecnológica em Saúde (Icict) da Fundação Oswaldo Cruz (Fiocruz), 2022)
There are several diseases transmitted by Aedes aegypti in Brazil. Campaigns run by federal, state and municipal governments and civil society organizations are one way to prevent Aedes aegypti contagion more effectively. The reach and effectiveness of these campaigns can be problematized through the analysis of the utterances they contain. Taking a discursive perspective and adopting the evidential paradigm, nine utterances from such campaigns were analyzed. The goal was to analyze the (persuasive) communication strategies used in Brazilian campaigns to prevent the spread of Aedes aegypti between 2013 and 2018. The analysis revealed discursive markers of authoritarianism and a disconnect between domestic and public spaces. The authoritarian nature is revealed in the use of language that holds citizens individually accountable for any potential non-participation in disease prevention, failing to assure the effective delivery of public health education.